Design of a Pisco Sour Vending Machine Based on an Embedded System (Raspberry Pi) - Achuy, Jesús (2022)
Pisco Sour is a traditional Peruvian cocktail made with pisco, egg white, sweetening syrup, and lemon juice. The preparation of this cocktail is made traditionally by a bartender following a recipe according to standardized preparation steps and quantities. The present research developed a vending machine to standardize the quantities of the ingredients, reduce the preparation time and guarantee the homogeneity of the product. The control is done with a Raspberry Pi 3, the dosing of the ingredients, through the development of different mechatronic systems, the pisco, sweetening syrup, and egg white enter through the use of peristaltic pumps to dispense exact amounts; it has a lemon squeezing and cutting system and, finally, the refrigeration system to keep all the ingredients fresh. The integration of the system avoids the loss of ingredients and reduces costs. As a result, the machine, compared to a bartender, maintains a uniform consumption of ingredients and a constant preparation time in a batch of more than 50 glasses of Pisco Sour.